2010
DOI: 10.5395/jkacd.2010.35.5.344
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical properties of experimental mixture of mineral trioxide aggregate and glass ionomer cement

Abstract: Objectives:The purpose of this study was to determine the setting time, compressive strength, solubility, and pH of mineral trioxide aggregate (MTA) mixed with glass ionomer cement (GIC) and to compare these properties with those of MTA, GIC, IRM, and SuperEBA. Materials and Methods: Setting time, compressive strength, and solubility were determined according to the ISO 9917 or 6876 method. The pH of the test materials was determined using a pH meter with specified electrode for solid specimen. Results: The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…In our case, the increased rate of setting time was dominantly caused by very small particles and crystallite sizes. Due to nanometric values of crystallite sizes (preferentially of calcium silicate phases), the setting time of our sample was significantly shorter, in comparison with data for MTA and Portland cement, found in literature …”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…In our case, the increased rate of setting time was dominantly caused by very small particles and crystallite sizes. Due to nanometric values of crystallite sizes (preferentially of calcium silicate phases), the setting time of our sample was significantly shorter, in comparison with data for MTA and Portland cement, found in literature …”
Section: Resultsmentioning
confidence: 55%
“…In the case of our new product ALBO‐MPCA, these values were 20 min for initial set time, while setting time was 50 min. ALBO‐MPCA evidently shows much better setting properties in comparison with Portland cement and MTA …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reports of Main et al confirm the superiority of MTA as a perforation repair material. [14][15][16][17] In our case, we used white MTA to repair the perforation, because of the potential discoloration effect of gray MTA. According to Asgary et al, the major difference between white MTA and gray MTA appears to be in the concentrations of carborundum, periclase, and especially ferrous oxide.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Nekoofar et al demonstrated that blood contamination influenced the development of MTA crystals and decreased its surface microhardness and compressive strength 3-5. It is well known that another disadvantage of MTA is its extended setting time 6-10…”
Section: Introductionmentioning
confidence: 99%